Prevalence of mutations linked to antimalarial resistance in Plasmodium falciparum from Chhattisgarh, Central India: A malaria elimination point of view. Issue 1 (December 2017) - Patel, Priyanka; Bharti, Praveen; Bansal, Devendra; Ali, Nazia; Raman, Rajive; Mohapatra, Pradyumna; Sehgal, Rakesh; Mahanta, Jagadish; Sultan, Ali; Singh, Neeru
Abstract Antimalarial drug resistance is a major global challenge in malaria control and elimination. Mutations in six different genes ofPlasmodium falciparum (crt, mdr1, dhfr, dhps, ATPase6 andK-13 propeller) that confer resistance to chloroquine, sulphadoxine-pyrimethamine and artemisinin-based combination therapy were analyzed in samples from Chhattisgarh. Seventy-eight percent of the samples were found to have apfcrt mutation (53% double, 24% triple and 1% single mutant), and 59% ofpfmdr1 genes were found to have an N86Y mutation. Double mutations were recorded inpfdhfr gene among 76% of the samples while only 6% of the samples harbored mutant genotypes inpfdhps . No mutation was found in theK-13 propeller gene, while only one sample showed a mutant genotype for thePfATPase6 gene. The Tajima test confirmed that there is no role of evolutionary natural selection in drug resistance, and gene pairwise linkage of disequilibrium showed significant intragenic association. The high level ofpfcrt mutations suggests that parasite resistance to chloroquine is almost at a fixed level, whereas resistance to SP is evolving in the population and parasites remain sensitive to artemisinin derivatives. These findings provide potential information and understanding of the evolution and spread of different drug resistance alleles in Chhattisgarh.